Aspirin plus clopidogrel versus aspirin mono-therapy for ischemic stroke: a meta-analysis. (4th July 2019) - Ye, Mao-Bin; Chen, Yan-Lin; Wang, Qin; An, Jun; Ye, Fei; Jing, Ping
Abstract: Objectives. Stroke is a common condition after a transient ischemic attack (TIA) or minor ischemic stroke (IS). Adding clopidogrel to aspirin may yield more beneficial outcomes than aspirin mono-therapy; meanwhile, the risk of bleeding in the acute phase remains poorly understood. Therefore, there is increasing emphasis on the risks and benefits of clopidogrel with aspirin compared with aspirin mono-therapy in an effort to treat TIA/IS. Design. We searched several electronic databases, including PubMed, Cochrane, and Embase, to identify eligible randomized controlled trials (RCTs) based on the index words comparing dual-antiplatelet therapy to aspirin mono-therapy for secondary stroke prevention updated to December, 2018. Results. A total of 11 RCTs met our inclusion criteria. The pooled analysis showed that clopidogrel plus aspirin was associated with a trend toward a reduction in recurrent IS (RR = 0.72, 95%CI = 0.65–0.81, p < .001), but not the recurrent stroke rate (RR = 0.81, 95% CI = 0.63‐1.03, p = .09) than aspirin mono-therapy. There were differences in bleeding episodes (RR = 1.81, 95%CI = 1.65–1.99, p < .001), moderate-severe major bleeding (RR = 1.64, 95% CI = 1.24‐2.16, p = .0005), or mild bleeding (RR = 2.25, 95%CI = 1.54–3.31, p < .001) between the study groups. Meanwhile, no benefit of reducing the risk of intracranial hemorrhage with dual-antiplatelet therapy was found in TIA/IS patients (RR = 1.44, 95% CI = 0.95–2.19, p = .09). Conclusions . The addition of clopidogrel to aspirin for patients with TIA or IS appeared to significantly reduce the risk of IS recurrence with a possible increase in the risk of bleeding compared with aspirin alone.